A Counseling Primer An Orientation to the Profession. - Guindon, Mary H.; Lane, Jessica J. (Milton : Routledge, 2019)
A Counseling Primer,second edition, introduces students to the profession of counseling, reviews its training curriculum, discusses current professional standards, and presents basic counseling skills. The text is designed to answer students' most commonly asked questions around the who, what, where, when, why, and how of counseling. Updated and aligned with the eight 2016 CACREP core areas, the second edition includes new chapters by experts from seven entry-level specialty areas, including school counseling, career counseling, and mental health counseling. The book also contains useful features to enhance the learning experience, including case examples, class handouts and activities, a sample syllabus, discussion questions, and more. A variety of online resources including instructor's manual, PowerPoint slides, tests, class activities, and student supplements are also available for download. In a comprehensive and accessible format, A Counseling Primer,second edition, provides students with a succinct, up-to-date picture of the counseling profession and the tools they need to make their contribution to the field.
Chapter 9 Addictions CounselingHistory of Addiction Counseling; Theories and Models of Addiction Counseling; Impact on the Individual, Family, and Community; Addiction Counseling Practices; Summary; References; Chapter 10 Career Counseling; History and Background; Terminology; Career Planning and Development Process; Job Search Process; Theories; Career Assessments; Summary; References; Chapter 11 Clinical Mental Health Counseling; History and Background of Clinical Mental Health Counseling; Theories and Models in Clinical Mental Health Counseling
Description based upon print version of record.
Impact on the Individual, Family, and Community
OCLC-licensed vendor bibliographic record.
Keywords: PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Education & Training; PSYCHOLOGY / Mental Health; Counseling psychology; Vocational guidance